KKN Tematik Terintegrasi “Pemberdayaan Masyarakat Kotesan melalui Optimalisasi Pendidikan, Edukasi Sosial Lingkungan, dan Pengembangan Inovasi Ekonomi Kreatif” - Putranto, Anggoro Bimo; Aliyah Ardhian Az Zahra; Satria Lafadz Wicaksana; Ancelin Aloysia Prasetyo; Suci Auliyya Alfir; Laksmi Aliyya Wismayadewi; Kalya Salsabila; Shofia Luthfi Dzulfahmi; Nadhifah Bayu Sukma; Aulia Anisa Az-Zahra; Ari Diana Susanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Livestock farming is an important sector in Indonesia, both economically and socially, in every community. The livestock sector supports and supplements the livelihoods of people who spend their days working in the fields. Small and large-scale livestock farming must be accompanied by an understanding of proper animal care and maintenance. Looking at the data and conditions in the field, especially in Kotesan Village, Prambanan District, many people still work in the agricultural sector and most of them have livestock such as goats and cows. Several incidents and deaths of goats and cows are also often found due to a lack of education about livestock care. There is a need for supplements and the fulfillment of livestock needs that are considered easy and basic. For this reason, the UNS 106 KKN team in Kotesan Village initiated the use of alternative feed as a supplement to the main feed in the form of silage and mineral blocks. Silage is used as a supplement and mineral blocks are used as additional nutrients to supplement the minerals needed by goats and cows. Until the training on making feed was held to educate farmers in Kotesan Village to prevent deaths due to paralysis and lack of livestock nutrition. With participants from the Joint Farmer Group in Kotesan Village, the UNS 106 Community Service Program team conducted training on making alternative livestock feed, namely silage and mineral blocks.